2015
DOI: 10.1038/pr.2015.217
|View full text |Cite
|
Sign up to set email alerts
|

Airway and alveolar nitric oxide production, lung function, and pulmonary blood flow in sickle cell disease

Abstract: Background: Children with sickle cell disease (SCD) often have obstructive lung function abnormalities which could be due to asthma or increased pulmonary blood volume; it is important to determine the underlying mechanism to direct appropriate treatment. In asthmatics, exhaled nitric oxide (F eNO ) is elevated. F eNO , however, can also be raised due to increased alveolar production. Our aim, therefore, was to determine if airway or alveolar NO production differed between SCD children and ethnic and age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Furthermore, FeNO measured at 50ml/sec was positively correlated with pulmonary blood flow but was not correlated with measures of airway obstruction or resistance, suggesting that some component of the FeNO of a SCD patient is due to increased alveolar NO production resulting from chronic anemia rather than airway inflammation from asthma. 40 In contrast, utilizing flow-independent methods, Radhakrishnan et al were able to determine that elevated FeNO levels among non-atopic children with SCD were higher compared to healthy controls, but their results showed that increase in FeNO originated in the bronchial tree and not from alveolar sources. 17 Further studies of FeNO in larger cohorts of SCD patients of varying ages and disease severity, with and without atopy, may clarify the relative contribution of airway and alveolar FeNO and possible associations with other markers of disease severity, such as endothelial dysfunction and markers of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, FeNO measured at 50ml/sec was positively correlated with pulmonary blood flow but was not correlated with measures of airway obstruction or resistance, suggesting that some component of the FeNO of a SCD patient is due to increased alveolar NO production resulting from chronic anemia rather than airway inflammation from asthma. 40 In contrast, utilizing flow-independent methods, Radhakrishnan et al were able to determine that elevated FeNO levels among non-atopic children with SCD were higher compared to healthy controls, but their results showed that increase in FeNO originated in the bronchial tree and not from alveolar sources. 17 Further studies of FeNO in larger cohorts of SCD patients of varying ages and disease severity, with and without atopy, may clarify the relative contribution of airway and alveolar FeNO and possible associations with other markers of disease severity, such as endothelial dysfunction and markers of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…19,39 Pawar et al noted that FeNO levels among patients during an acute VOC pain episode were no different than among those at steady state. 19 A recent study of FeNO measured at variable flow rates 40 found elevated alveolar NO concentration and production among SCD patients compared to healthy race-matched controls. They also found significant positive correlations between alveolar NO and pulmonary blood flow in the SCD group, suggesting that alveolar NO production is related to the chronic hyperdynamic circulation found in patients with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study of 18 SCD children compared to 18 ethnic and age-matched controls, the SCD children had a significantly higher respiratory system resistance, alveolar NO production and pulmonary blood flow, but not airway NO flux. There was a significant correlation between alveolar NO production and pulmonary blood flow, but not between airway NO flux and respiratory system resistance [66]. SCD patients have an increased pulmonary capillary blood volume resulting from their chronic anaemia.…”
Section: Aetiology Of the Lung Function Abnormalitiesmentioning
confidence: 82%
“…Exhaled nitric oxide, a marker of asthma and steroid response, is reduced in SCD patients [72]. Comparison of SCD children with age-and ethnicity-matched controls demonstrated the former did not have elevated airway nitric oxide flux nor did the levels correlate with airways obstruction [73].…”
Section: Potential Mechanisms For Reactive Airways Disease In Scdmentioning
confidence: 93%